Advancements in zeolite-based catalysts for the isomerization of n-alkanes: mechanistic insights and future directions - Nastaran Parsafard; Zaidoon M. Shakor (Discover Applied Sciences)
Abstract In recent years, the isomerization of n-alkanes has garnered significant attention due to its pivotal role in enhancing the octane number of gasoline and producing valuable chemicals. This study delves into the advancements in zeolite-based catalysts, specifically tailored for the isomerization of n-alkanes, offering mechanistic insights and outlining future research directions. Leveraging a combination of experimental and computational approaches, we systematically investigate the influence of zeolite framework topology, active site configuration, and reaction conditions on catalytic performance. Our findings underscore the critical role of acid–base properties and pore architecture in dictating selectivity and conversion rates. Notably, we identify a novel class of hierarchical zeolites that exhibit superior activity and stability compared to conventional counterparts, attributed to enhanced mass transport and optimized active site accessibility. Additionally, we elucidate the underlying mechanisms governing the isomerization process over these catalysts, revealing intricate relationships between structural characteristics and reactivity patterns. Based on these insights, we propose strategic modifications to zeolite catalysts that could lead to breakthroughs in efficiency and sustainability of n-alkane isomerization processes. Looking ahead, we discuss potential pathways for integrating these advanced catalysts into industrial settings, alongside challenges and opportunities for future research in the realm of zeolite-catalyzed reactions. This work not only contributes to the fundamental understanding of zeolite catalysis but also paves the way for the development of next-generation catalysts for energy-efficient chemical transformations.